Kualitas Pelayanan Kantor POS Ujung Berung Sebagai Upaya Menjaga Eksistensi Di Era Pandemi Covid-19 - Anisa Novita Sari; Engkus; Faizal Pikri (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2022)
The Quality of Service of the Ujung Berung Post Office as an Effort to Maintain Existence in the Era of the Covid-19 Pandemic. Having a purpose as an evaluation material for the Ujungberung Post Office and knowing the level of service quality of the Ujungberung Post Office in the era of increasingly widespread expedition development. If efforts are made to improve services according to customer needs, it will affect customer satisfaction. Collecting data in the field using a qualitative descriptive method. Data collection techniques using: observation, interviews and documentation. Data were analyzed using data reduction, presentation and conclusion techniques and supported by 5 dimensions, namely Tangiable (real evidence), Empathy (Empathy), Reliability (Reliability), Responsivines (Responsiveness), and Assurance (Assurance). The results of this study indicate that the quality of services provided by the Ujungberung Post Office is categorized as not optimal because in the study of the dimensions of physical evidence (Tangiable) it is still not good because some employees are not on time for work hours, then there are MSME stands that are not used properly. . And in the dimension of Reliability (Reliability) obtained interviews with customers who complained about late arrivals. Kualitas Pelayanan Kantor Pos Ujung Berung Sebagai Upaya Menjaga Eksistensi di Era Pandemi Covid-19. Memiliki tujuan sebagai bahan evaluasi terhadap Kantor Pos Ujungberung serta mengetahui tingkat kualitas pelayanan Kantor Pos Ujungberung di era perkembangan ekspedisi yang semakin marak. Jika dilakukan upaya peningkatan pelayanan sesuai kebutuhan pelanggan, maka akan mempengaruhi kepuasan pelanggan. Pengumpulan data di lapangan menggunakan metode deskriptif kualitatif. Teknik pengumpulan data menggunakan: observasi, wawancara dan dokumentasi. Data dianalisis menggunakan teknik reduksi data, penyajian dan penarikan kesimpulan serta didukung oleh 5 Dimensi yaitu Tangiable (bukti nyata), Empaty (Empati), Reability (Kehandalan), Responsivines (Daya Tanggap), dan Assurance (Jaminan). Hasil dari penelitian ini menunjukan bahwa kualitas layanan yang diberikan oleh Kantor Pos Ujungberung dikategorikan belum optimal karena dalam kajian dimensi bukti fisik (Tangiable) masih kurang baik karena beberapa karyawan tidak tepat waktu untuk jam masuk kerja, lalu ada stand UMKM juga yang tidak dipergunakan dengan baik. Dan di dimensi Reabilty (Kehandalan) didapat wawancara pelanggan yang mengeluhkan barang telat datang.